PERANCANGAN SISTEM INFORMASI PEMESANAN TIKET BUS DAMRI DI BANDARA XYZ MENGGUNAKAN QR CODE DAN WEB BASE - Gintya Purna Wibowo; Hari Purwanto (Fakultas Ilmu Komputer dan Desain - Unsurya, 2020)
ABSTRACTAdvances in technology requires a human tasks that are still manual and less efficient to do with technology. Should be further enhanced using modern systems. The computerized system can help speed things done. The manual system is still widely used in the world of work. If observed using a computerized system that has not yet much less effective in the working process. In general, these companies are still not using internet technology to the maximum. The problems faced by this company that issues the reserve tickets are still using manual resulting in rather long queue just to book a bus ticket Damri at XYZ airport. Bus ticket booking information system Damri an information medium that offers the ease of ordering a bus ticket Damri. One technology that is used in making the bus ticket booking information system Damri at XYZ Airport is Personal Home Page (PHP) and MySQL using Dreamweaver.Â Keywords: Information Systems, Information Systems Bus Ticket Booking, Website, PHP, MySQL.